Three-Dimensional Arterial Distribution Over the Midline of the Nasal Bone. (31st December 2021) - Cong, Li-Yao; Liao, Zhi-Feng; Zhang, Yun-Song; Li, Dong-Ni; Luo, Sheng-Kang
Abstract: Background: A comprehensive understanding of arterial variations around the midline of the nose is of great importance for the safety of filler injection. Objectives: The aim of the study was to clearly define the 3-dimensional location of the arteries along the midline of the nasal bone. Methods: The arterial structures overlapping the nasal bone along the midline were observed in 79 cadavers. Results: The present study found that 0 to 3 named arteries per nose segment could be identified. All the arterial structures were located in or above the superficial musculoaponeurotic system layer overlapping the nasal bone. The probability of encountering named arteries at 5 defined points, P1 to P5, was 5/79 (6.3%), 4/79 (5.1%), 1/79 (1.3%), 6/79 (7.6%), and 9/79 (11.4%), respectively. The depth of the main arterial trunk was 1.2 ± 0.4 mm, 1.6 ± 0.6 mm, 1.8 ± 0 mm, 1.0 ± 0.4 mm, and 0.9 ± 0.5 mm below the skin at P1 to P5, respectively. Conclusions: The authors confirmed that sub-superficial musculoaponeurotic system injection along the midline through a needle is anatomically reliable and that a technique with 1 entry point through the rhinion via a cannula can easily keep the needle sufficiently deep for safe nasal filler injection.